Adhesion of monocytes to periodontal fibroblasts requires activation of NOD1/2- and TLR4-mediated LFA-1 and VLA-4. Issue 6 (June 2015) - Liu, Jianru; Liu, Wenyi; Xie, Ying; Wang, Yixiang; Ouyang, Xiangying
Highlights NOD1/2 and TLR 4 were highly expressed in the gingiva of patients with periodontitis. NOD1/2 and TLR4 regulated the activity of LFA-1 and VLA-1 in cells of U937. NOD1/2 and TLR4 mediated the binding of U937 cells to periodontal fibroblasts. LFA-1 and VLA-4 are responsible for monocyte-periodontal fibroblasts adhesion.